Perinatal undernutrition programmes thyroid function in the adult rat offspring. Issue 12 (26th June 2013) - Ayala-Moreno, Rosario; Racotta, Radu; Anguiano, Brenda; Aceves, Carmen; Quevedo, Lucía
Abstract : Increasing evidence suggests that alterations in early nutrition programme physiological changes in adulthood. In the present study, we determined the effects of undernutrition during gestation and lactation on the programming of thyroid function in adult rat offspring. Perinatal undernutrition was achieved by a 40 % food restriction in female Wistar rats from the mating day to weaning. On postpartum day 21, the offspring of the control and food-restricted dams were weaned and given free access to a commercial diet until adulthood. The results showed that undernourished rats exhibited decreased 3, 5, 3′-triiodothyronine (T3 ) levels but had normal thyroxine (T4 ) and thyrotropin (TSH) levels at weaning; on day 90, these rats displayed a significant flip, exhibiting normalised T3 (total and free) and total T4 levels, but low free T4 and persistently higher TSH levels, which were maintained even on postnatal day 140. This profile was accompanied by a scarce fat depot, a lower RMR and an exacerbated sympathetic brown adipose tissue (BAT) tone (deiodinase type 2 expression) in basal conditions. Moreover, when a functional challenge (cold exposure) was applied, the restricted group exhibited partial changes in TSH (29 v. 100 %) and T4 (non-response v. 17 %) levels, a significant decrease in leptin levels (75 v . 32 %) and the maintenance of a sympathetic BAT over-response (higher noradrenaline levels) in comparison with the control group. The findings of the present study suggest that undernutrition during the perinatal period produces permanent changes in the hypothalamus–pituitary–thyroid axis with consequent low body weight and decreased RMR and facultative thermogenesis. We hypothesise that these changes predispose individuals to exhibiting adult subclinical hypothyroidism.